Cesàro Summability Involving $δ$-Quasi-Monotone and Almost Increasing Sequences - Bağdagül Kartal (Journal of New Theory)
This paper generalises a well-known theorem on ${\mid{C},ρ\mid}_κ$ summability to the $φ-{\mid{C},ρ;β\mid}_κ$ summability of an infinite series using an almost increasing and a $δ$-quasi monotone sequence.